Glial Fibrillary Acidic Protein Astrocytopathy in Pediatric Patients: A Retrospective Study - Huang, Haixia; Bai, Ke; Fu, Yueqiang; Lu, Siwei; Ran, Yunni; Dang, Hongxing; Li, Jing (Frontiers in Pediatrics, 2021)
Autoimmune glial fibrillary acidic protein astrocytopathy is a novel form of autoimmune meningoencephalitis related to GFAP autoantibodies. This condition is still being characterized, and few pediatric patients have been identified. Here, we report three patients presenting with fever, nausea, and headache, following progressive disturbance of consciousness, limb weakness, dyspnea, or urine retention. MRI analysis revealed that T2-hyperintense lesions, or enhancement of the meninges and spinal cord. CSF and serum analyses revealed they were positive for GFAP antibody, confirming GFAP astrocytopathy diagnosis. Treating the patients with IVIG, with or without intravenous steroids, gradually improved their clinical symptoms. Our findings indicate that GFAP astrocytopathy should be considered in children who are clinically diagnosed with meningoencephalitis, whether or not myelitis is present, and if the MRI reveals enhancement of meninges or spinal cord, T2-hyperintense lesions, or a pattern of linear perivascular gadolinium enhancement. Suspected cases should be tested for GFAP antibody as soon as possible because these patients may benefit from immunotherapy.